2011
DOI: 10.4300/jgme-d-11-00036.1
|View full text |Cite
|
Sign up to set email alerts
|

Reflection in a Museum Setting: The Personal Responses Tour

Abstract: Introduction We describe an educational innovation piloted by the director of education at a university art museum and a physician-educator using the museum holdings as reflective triggers for medical learners. This innovation is distinct from the emerging trend of using art to build observation skills, enhance pattern recognition, and improve diagnostic acumen. Our intervention is specifically designed to promote individual reflection, foster empathy, increase appreciation for the psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] The educational objectives of these offerings vary widely, from more practical uses such as sharpening observational skills 1,[12][13][14] and teaching anatomy, 15 to stimulating reflection on the experience of illness and the nature of doctoring. 3,5 Furthermore, ways in which art is used similarly run the gamut from studying works of art in museums to the creation of art by students; however, studies assessing the educational significance of these efforts are few in number. 5,[16][17][18] One of the authors (AKK) has previously theorised about the educational functions of creative art in medical education.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] The educational objectives of these offerings vary widely, from more practical uses such as sharpening observational skills 1,[12][13][14] and teaching anatomy, 15 to stimulating reflection on the experience of illness and the nature of doctoring. 3,5 Furthermore, ways in which art is used similarly run the gamut from studying works of art in museums to the creation of art by students; however, studies assessing the educational significance of these efforts are few in number. 5,[16][17][18] One of the authors (AKK) has previously theorised about the educational functions of creative art in medical education.…”
mentioning
confidence: 99%
“…3,5 Furthermore, ways in which art is used similarly run the gamut from studying works of art in museums to the creation of art by students; however, studies assessing the educational significance of these efforts are few in number. 5,[16][17][18] One of the authors (AKK) has previously theorised about the educational functions of creative art in medical education. The creation of original artwork by medical students, he argued, allowed access to thoughts, feelings and impressions that students may acquire in interacting with families who live with chronic illness.…”
mentioning
confidence: 99%
“…30 Reflection and reflective practice are regarded as important parts of the experiential learning processes and have been shown as essential to the development of medical professionalism related to humanism, building individual reflection, fostering empathy, increasing understanding and appreciation for the community and the society, building community, and enhancing cultural competence. [31][32][33][34] Many kinds of reflection exercises have been reported to stimulate and motivate reflection on specific issues. 35 Our data indicated that students were motivated to reflect on their development as physicians through experiential leaning.…”
Section: Discussionmentioning
confidence: 99%
“…Group interpretive exercises allow learners to explore team dynamics and examine medical thinking processes. New strategies, such as the ‘personal responses tour’ (PRT), 1 use artwork in museum settings as triggers for reflection, a core competency for medical professionals.…”
mentioning
confidence: 99%